Normas y reglas de comportamiento para la convivencia - Tipán Defaz, Martha Cecilia (2020)
Assertive communication allows mediating difficulties and negative behaviors, helping to maintain a harmonious coexistence among classmates. The present research study on the policies and rules of behavior of coexistence of level 2 preschool children, in the "Juan de Salinas" School, is carried out based on a direct observation of the problem. In this study, exploratory, diagnostic and descriptive research was used, based on qualitative and quantitative techniques, which, by comparing and contrasting theories, helped to gather information on the research problem. Once the theories of coexistence policies and rules of behavior have been analyzed, a methodological guide is developed to improve children's coexistence. The proposal contains several strategies to improve certain disruptive behaviors of preschool children, for example, inappropriate behavior in the classroom (physical and verbal aggression, tantrums) and disobedience to the policies and rules established by the teacher. The proposal validated by experts, with experience in the area, certifies its validity and relevance. The guide applied to level 2 preschool children, between four and five years old, improved the children's behavior. Create a harmonious environment by practicing assertive communication with classmates and teachers. Therefore, the children learned to respect the individual differences of their peers, practicing the value of empathy.